ISSUES OF FINANCING LITHUANIAN HIGHER EDUCATION INSTITUTIONS - Greičius, Saulius; Pranevičienė, Birutė; Pūraitė, Aurelija; Margevičiūtė, Agnė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Higher education of Lithuania and its legal regulations constantly undergo various changes – both necessary and timely, as well as quite chaotic and fragmented. There have recently been a number of reforms implemented in the field of higher education in Lithuania, related to the financing of higher education, management, transformations of the influence of the state institutions on higher education institutions. The new reform of the whole system of higher education is being planned to begin in 2017, it is announced that there will be a drastic decrease in the number of public institutions of higher education and this should lead to improvement of the quality of studies and to better allocation of state finances. The object of the research is features and problems of the financing of higher education in Lithuania. The aim of the research is to present the system of higher education in Lithuania, to evaluate trends in financing of higher education and to determine shortages of legal regulation of this field, disclose problems related to dysfunctions of legal regulations and shortcomings of practical applications. After analysing the main provisions of the financing reform of higher education in Lithuania and evaluating the first results of the reform, conclusions regarding the main shortages and advantages of the reform are provided, other financing alternatives for higher education are suggested.